Estado e a produção de energia elétrica no Brasil: a organização coletiva dos produtores rurais atingidos por barragens do Rio Iguaçu no Oeste e Sudoeste do Paraná - Barros, Marcio José de (2020)
The dissertation State and the production of electric energy in Brazil: The collective organization of rural producers affected by dams on the Iguaçu River in the West and Southwest of Paraná, developed at the Western Paraná State University - UNIOESTE, campus of Cascavel/PR, in the research line “Education, Social Policies and the State”, aims to analyze the relationship that the “democratic State” of law establishes with the dominant society and those citizens affecte by the process of building hydroelectric plants in order to review if whether there are political interests, economic and political parties that influence the constitution, maintenance and/or dissolution of the Social Movement of People Affected by Dams in the West and Southwest of Paraná, more specifically in the social movements of Salto Caxias and Baixo Iguaçu. For this purpose, this study was based primarily on the bibliographic and documentary methodology according to based on scholars and documents such as Laws, Decrees and Resolutions, but it directs its structuring axis to the social and qualitative research field which was carried out through the application of interviews, supported by semi-structured questionnaires, applied to producers and rural producers affected by the aforementioned Hydroelectric Plants, thus making it possible to give voice to those citizens to express their stories, perceptions and experiences. Theoretically, hydroelectricity production is the basis for maintaining the economic growth by fostering the industrial sector, and gains visibility on the premise of a less aggressive energy source, as it meets environmental as well as social legislation regarding those affected by hydroelectric works. However, through the analyzes carried out and the data collected by our research, it can be seen that the use of water sources is rigidly constructed with environmental and social public policies, but the political and economic interests that permeate these actions distort the application of these guidelines in social practices, where those affected are demeaned and forced to either accept the imposed determinations or to promote a movement of social organization searching for defense and guarantee of rights. The results of this study offer important inputs to our society and especially to social movements that enable to reflect on dominant interests and social service. In this ways they can be ways to guide survival actions and social empowerment concerning the promotion of the guarantee and defense of rights.